Mucins and NCAM (CD56) in intrahepatic cholangiocarcinogenesis - Anna Beatriz Telles Esperança; Aline Helen da Silva Camacho; Juliana Bigi Maya Monteiro; Geysa Bigi Maya Monteiro; Adriana Caroli-Bottino; Vera Lucia Nunes Pannain (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction: Cholangiocarcinoma is the second most common malignant neoplasm of the hepatobiliary system. During cholangiocarcinogenesis phenotypic changes occur in the ductal epithelium, including the expression of mucins (MUC). However, the evaluating studies of the expression of mucins in the different stages of cholangiocarcinogenesis are scarce. CD56 has also contributed in differentiating benign ductal proliferation and cholangiocarcinoma; however, its expression has not been evaluated in dysplastic epithelium of the bile duct yet. Objective: To assess immunohistochemical profile of (MUC) 1, 2, 5, 6, and CD56 in cholangiocarcinoma, pre-neoplastic and reactive lesions in the epithelium of intrahepatic bile ducts. Material and methods: Immunohistochemical expression of MUC 1, 2, 5, 6, and CD56 were studied for 11 cases of cholangiocarcinoma and 83 intrahepatic bile ducts (67 reactive and 16 dysplastic). Variables were considered significant when p < 0.05. Results: The expression of MUC1 occurred in about 90% of the cholangiocarcinomas, contrasting with the low frequency of positive cases in reactive and dysplastic bile ducts (p < 0.001). However, there was no statistically significant difference in the expression of MUC5, MUC6 and CD56 between the reactive or dysplastic lesions and cholangiocarcinoma. The anti-MUC2 antibody was negative in all cases. Conclusions: MUC1 contributed for the differential diagnosis between cholangiocarcinoma and pre-neoplastic and reactive/regenerative lesions of intrahepatic bile ducts, and it should compose the antibodies panel aiming at improvement of these differential diagnoses. In contrast, MUC2, MUC5, MUC6 and CD56 were not promising in differentiating all the phases of cholangiocarcinogenesis.